Antibiofilm Activity of a Thermoformable Material Loaded With Essential Oil Solution - Alexandra Stähli; Markus Laky; Anton Sculean; Tino Töpper; Sigrun Eick (Clinical and Experimental Dental Research, 2026)
ABSTRACT Background Interest in antimicrobial surfaces for dental devices, such as aligners and brackets, is growing. These surfaces are designed to retard biofilm formation. One approach is to load essential oils (EOs) into the material. The focus of this study was the antibacterial, anti‐biofilm, and anti‐inflammatory activities of an EO solution. Methods The EO solution contained cinnamaldehyde, methyl salicylate, eucalyptol, limonene, and trans‐anethole dissolved in distilled water (dH 2 O) with polyglycerol‐4‐laurate/sabacate (basic solution). The positive control was 0.2% chlorhexidine digluconate (CHX). The antibacterial activity of the EO and the basic solution was tested against selected oral bacteria. Multispecies biofilms were formed on specimens of a cellulose‐based (test) material loaded with the EO solution or the basic solution, and on a polyurethane‐based (reference) material loaded with CHX. The level of IL‐8 released from gingival fibroblasts (GF) exposed to the solutions was measured. Results The EO solution clearly inhibited bacterial growth. However, the basic solution also acted as a growth inhibitor at higher concentrations. The EO solution reduced the metabolic activity of the formed biofilm. In addition, the basic solution decreased biofilm mass and colony‐forming unit counts. The basic solution was not inferior to CHX on the reference material. However, only the basic solution, not the EO solution, suppressed the release of IL‐8 from GF when stimulated with bacteria. Conclusion Applying essential oils (EOs) to surfaces may be an effective way to inhibit biofilm formation. The basic solution, which is polyglyceryl‐laurate‐based, exhibits anti‐biofilm and anti‐inflammatory properties. Further in vitro research should aim to gain a deeper understanding of the solubilizer's mechanisms and optimize the composition of the added essential oils before testing in clinical trials.